PLAYFULNESS AND ITS CONTRIBUTIONS TO EVALUATION IN EARLY CHILDHOOD EDUCATION - Ramos Pereira de Souza, Diego; Alexandre Agreli de Lira Miranda, Ricardo; da Silva Costa, Jucelino; Marcia de Mendonça Oliveira, Girlaine; Aparecida Santos da Silva, Maria; Wilker da Silva, José; de Gouvêa Caldas, Glauco; Maria do Nascimento Domingos, Ramires; Maria Alves, Ivanilda; Bruna da Silva, Maria; de Melo Silva, Inaldevania (Revista Gênero e Interdisciplinaridade, 2025)
The article Psidcusses the importance of School-Family interaction in the process of developing the child’s learning to a quality education. The methodology used was bibliographical research, in which it was verified that the relation of the school is indispensable the family must provide guidelines, construction of the identity of an individual should promote together with the school a partnership, in order to contribute in the integral development of the child. The research aimed to investigate the importance and influence of the family in the children’s school performance. Considering that it is during the process of literacy that the relation school and family stands out.